Gestão e salvaguarda do património arqueológico: o caso da Universidade de Évora (Portugal) - Rocha, Leonor (2020)
We are interested, for the present study, the issues inherent to the architecture of these spaces that today belong to the University of Évora, and that since 1979 have had several works of requalification with the intention of improving spaces, accessibility, to place and / or remodel infrastructures or other type of supports. It should be noted that most of the works that took place in this space until the end of the 19th century. XX, in spite of the fact that they involved land modulations (such as in the Granite Garden), the closing of wells, the opening of ditches for the passage of pipes and cables, did not have any archaeological accompaniment. We aim, on the one hand, to recover lost memories and, on the other hand, to give knowledge of the results obtained with the archaeological accompaniments realized in recent years, in buildings of the Évora University.